Inside Cover: Free Carrier Generation in Organic Photovoltaic Bulk Heterojunctions of Conjugated Polymers with Molecular Acceptors: Planar versus Spherical Acceptors (ChemPhysChem 8/2014). Issue 8 (6th June 2014) - Nardes, Alexandre M.; Ferguson, Andrew J.; Wolfer, Pascal; Gui, Kurt; Burn, Paul L.; Meredith, Paul; Kopidakis, Nikos
<x xml:space="preserve">Abstract</x> On p. 1539 N. Kopidakis et al. present a comparative study of the photophysical performance of a prototypical fullerene derivative with a planar small molecule acceptor in an organic photovoltaic device. The shapes of the molecules determine the performance of the device in more than one way.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>